INTEGRASI PENDIDIKAN AGAMA ISLAM DAN SAINS DALAM MENINGKATKAN MUTU PENDIDIKAN SERTA MEMBANGUN BRAND IMAGE ( Studi Kasus di MA Persis Sindangkasih Ciamis ) - Rifyal Luthfi (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2023)
This thesis aims to analyze and document the implementation of the integration of Islamic religious education and science in improving the quality of education and building brand image at MA Persis Sindangkasih Ciamis. This research uses a qualitative approach with case study as the research method. Data were collected through participatory observation, in-depth interviews, and analysis of related documents.The results showed that MA Persis Sindangkasih Ciamis has successfully implemented the integration of Islamic religious education and science well. This integration can be seen in lesson planning, curriculum development and teaching methods used. This approach creates a holistic educational environment and helps students develop a comprehensive understanding of Islamic religion and science. The research also identified some challenges in implementing the integration of Islamic religious education and science, including a lack of resources, challenges in integrating the curriculum and the need for training and coaching for teachers. However, through collaboration between the school, teachers, students and relevant stakeholders, MA Persis Sindangkasih Ciamis managed to overcome these challenges. In conclusion, the integration of Islamic religious education and science at MA Persis Sindangkasih Ciamis provides significant benefits in improving the quality of education and building the institution's brand image. This study provides a deeper understanding of the practical implementation of such integration and contributes to the development of education in Indonesia. Recommendations are made for other educational institutions that wish to implement similar integration, including the need for adequate resource support and training for teachers